EFL Students’ Perspective on the Usefulness of ICT based Learning in Indonesian Higher Education - Muhammad Basri; Muhammad Azwar Paramma (Pascasarjana Universitas Negeri Makassar, 2019)
The study explores the perception of the EFL students in English Language Teaching through ICT based learning at Universitas Negeri Makassar. It employs a descriptive study using purposive sampling techniques by taking 57 respondents from university students. The online questionnaire used to collect data on the perception of students on the ICT based Learning of English Language Teaching. The method of descriptive in terms of percentage has been used for data processing, and the deduction method has been used to analyze and interpret data. The result of this study indicates the positive perception those university students hold on the use of the Learning Management System in English Language Teaching. Further study can refer to this Acceptance Model in determining a suitable ICT integrated learning program between the reality and user expectations of the program used.